Predictive factors of Permanent Pacemaker Implantation following Transcatheter Aortic Valve Replacement: membranous septum length and implantation depth evaluated with preoperative computed tomography. (14th October 2021) - Ciatti, F; Stolcova, M; Romano, C D; Mattesini, A; Ristalli, F; Demola, P; Meucci, F; Di Mario, C
Abstract: Background/Introduction: In the last decades, transcatheter aortic valve replacement (TAVR) revolutionized the treatment of symptomatic severe aortic stenosis. Cardiac conduction disturbances (CD) and the need for permanent pacemaker implantation (PPMI) remain the most frequent drawback of TAVR.The efficacy and safety of TAVR is proven not only in inoperable and high-risk patients, but TAVR use is increasing rapidly among intermediate- and low-risk populations, including progressively younger patients. In these prospective the risk of new-onset CD becomes increasingly important in clinical management. Several pre-procedural nonmodifiable factors (e.g., right bundle branch block [RBBB]) and modifiable factors (such as valve type and implantation depth) have been associated with conduction disturbances post-TAVR. Purpose: The His bundle passes through the membranous septum (MS) and it is therefore not surprising that deeper valve implantation increases the likelihood of mechanical damage of the His bundle, leading to a transient or persistent CD. To date, it remains uncertain whether the association between valve type and CD relates primarily to a valve class effect or it is mainly secondary to differences in valve positioning accuracy and implantation depth between valve types. The aim of this study is to evaluate the length of the membranous septum (MS) and the implant depth (ID) in relation to the risk of permanent pacemaker (PPM) with both balloon-expandable (BE) and self-expanding (SE) transcatheter heart valves. Methods: Of the 104 patients in the study, 79 patients underwent TAVIs with BE (44) and SE valves (35). Using preoperative computed tomography (CT) and angiography, MS length and implantation depth (ID) were retrospectively assessed. 14 patients were excluded for the presence of pre-TAVI PPM, 3 for the presence of congenital bicuspid aortic valve, 8 due to the presence of non-evaluable CT angiography. Results: In the study population, out of the total of 79 patients, PPMs were implanted in 8 patients (10.12%), of which 7 in 35 (20%) patients undergoing TAVI with SE and 1 in 44 (2.27%) with BE valves. The measurements of MS was 4±2.1 mm for BE vs 3.3±2 mm for SE valves (p=0.141) and ID was 4.9±1.7 mm for BE vs 5.9±3.2 mm for SE valves (p=0.046). At multivariate logistic regression, two significant variables related to the post-TAVI PPMI were identified: MS (p=0.029) and ID (p=0.009), moreover the MS / ID ratio represents an additional predictor for PPMI regardless of the type of valve used (p=0.002). Conclusion(s): The study confirms the importance of the pre-TAVI MS length measurement for both types of valves. The only modifiable factor is the implantation technique which, knowing the PPMI's preoperative risk must be modified according to the patient's septum. Therefore it will be possible to modify the valve ID according to the patient's septum, looking for higher implants in higher-risk cases, particularly with self-expanding valves. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): No fundings